2014
DOI: 10.1371/journal.pone.0113924
|View full text |Cite
|
Sign up to set email alerts
|

IgG Antibodies to Cyclic Citrullinated Peptides Exhibit Profiles Specific in Terms of IgG Subclasses, Fc-Glycans and a Fab-Peptide Sequence

Abstract: The Fc-glycan profile of IgG1 anti-citrullinated peptide antibodies (ACPA) in rheumatoid arthritis (RA) patients has recently been reported to be different from non-ACPA IgG1, a phenomenon which likely plays a role in RA pathogenesis. Herein we investigate the Fc-glycosylation pattern of all ACPA-IgG isotypes and simultaneously investigate in detail the IgG protein-chain sequence repertoire. IgG from serum or plasma (S/P, n = 14) and synovial fluid (SF, n = 4) from 18 ACPA-positive RA-patients was enriched usi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
48
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 35 publications
(55 citation statements)
references
References 52 publications
(77 reference statements)
5
48
1
Order By: Relevance
“…Interestingly, the Fab-glycosylation pattern of ACPA-IgG showed a significantly higher frequency of galactose, sialic acid and fucose residues as compared with that of control IgG depleted of ACPA. These high galactosylation and sialylation levels of the Fab-linked glycans are in clear contrast to the lower level of Structural Analysis of ACPA-IgG Fab-glycosylation galactosylation and sialylation previously detected in the Fcpart of ACPA-IgG (23,28,29). Therefore, our data show that the changes in antibody glycosylation occurring during RA are not only (auto)antibody-specific, but also site-specific.…”
Section: Acpa-igg Exhibit a Higher Level Of Fab Glycosylation-wecontrasting
confidence: 77%
See 1 more Smart Citation
“…Interestingly, the Fab-glycosylation pattern of ACPA-IgG showed a significantly higher frequency of galactose, sialic acid and fucose residues as compared with that of control IgG depleted of ACPA. These high galactosylation and sialylation levels of the Fab-linked glycans are in clear contrast to the lower level of Structural Analysis of ACPA-IgG Fab-glycosylation galactosylation and sialylation previously detected in the Fcpart of ACPA-IgG (23,28,29). Therefore, our data show that the changes in antibody glycosylation occurring during RA are not only (auto)antibody-specific, but also site-specific.…”
Section: Acpa-igg Exhibit a Higher Level Of Fab Glycosylation-wecontrasting
confidence: 77%
“…ACPA-positive RA is characterized by a high rate of joint erosions and a low chance to achieve remission when left untreated (15). Earlier, we and others reported that the galactosylation and sialylation levels of Fc-glycans from ACPA-IgG is lower compared with control IgG, and this is more pronounced in ACPA-IgG isolated from SF (28,29). In addition, we observed that the changes of ACPA-IgG Fcglycosylation already occur a few months before of the diagnosis of RA (23).…”
Section: Acpa-igg Exhibit a Higher Level Of Fab Glycosylation-wementioning
confidence: 93%
“…Future work detailing glycan profiles of DSA would determine if antibody glycosylation status correlates with severity of AMR. Additionally, new methodology described to simultaneously measure both the subclass and glycosylation of antigen-specific IgG [94] may be adapted to transplantation.…”
Section: Regulation Of Igg Glycosylationmentioning
confidence: 99%
“…Among these, glycoprofile changes among antigen-specific antibodies over time following vaccination have been observed (Selman et al, 2012), and a role for T cell help in modulating IgG glycosylation defined (Hess et al, 2013; Oefner et al, 2012). In addition, altered glycosylation of virus-specific IgG has been associated with altered antiviral antibody function among HIV-infected subjects (Ackerman et al, 2013), anti-citrullinated peptide/protein antibodies (ACPA) isolated from subjects with rheumatoid arthritis have been observed to posses altered glycosylation that can precede disease onset and differ between serum and within synovial fluid (Lundstrom et al, 2014; Rombouts et al, 2015a; Scherer et al, 2010), and glycovariation among anti-proteinase 3 antibodies has been found to correlate with disease activity as determined by clinical vasculitis score (Wuhrer et al, 2015). Successful allergy immunotherapy has been associated with the induction of sialylated allergen-specific antibodies (Oefner et al, 2012).…”
Section: Discussionmentioning
confidence: 99%